2020
DOI: 10.1038/s41467-020-17257-7
|View full text |Cite
|
Sign up to set email alerts
|

Phasic dopamine reinforces distinct striatal stimulus encoding in the olfactory tubercle driving dopaminergic reward prediction

Abstract: The learning of stimulus-outcome associations allows for predictions about the environment. Ventral striatum and dopaminergic midbrain neurons form a larger network for generating reward prediction signals from sensory cues. Yet, the network plasticity mechanisms to generate predictive signals in these distributed circuits have not been entirely clarified. Also, direct evidence of the underlying interregional assembly formation and information transfer is still missing. Here we show that phasic dopamine is suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 74 publications
2
36
0
Order By: Relevance
“…S6A ). Considering that the CS-bound value coding units are reinforced from pre-existing odor-specific responses (Oettl et al, 2020), we wondered whether the single-units not encoding monotonic RP still contributed collectively to it. Indeed, upon removal of all units with monotonic RP coding in the transient-cluster, the cumulative firing rate of the remaining units still reflected a robust population coding of the monotonic RP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S6A ). Considering that the CS-bound value coding units are reinforced from pre-existing odor-specific responses (Oettl et al, 2020), we wondered whether the single-units not encoding monotonic RP still contributed collectively to it. Indeed, upon removal of all units with monotonic RP coding in the transient-cluster, the cumulative firing rate of the remaining units still reflected a robust population coding of the monotonic RP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that Tu neurons are recruited by stimuli that predict rewards upon conditioning (Gadziola et al, 2020, Millman and Murthy, 2020, Murata et al, 2015, Oettl et al, 2020, Zhang et al, 2017). In these studies, the duration of the conditioned stimulus partially overlaps with US.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations